(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: To find out the incidence and types of complications after thyroidectomy.To analyze the factors related to the complications of thyroid surgery. Material and method: The study was carried out at Shahid Suhrawardy medical college and Hospital, Dhaka from July 2007 to June 2008. Fifty patients were selected for the study who were treated by thyroidectomy. The mean patient’s age at the time of surgery was 41.9±8.1 years ranged from 10 to 60 years. Data were collected in a prescribed data collection sheet. Then all data were compiled and analyzed. Result: 12% of the patients had transient hypoparathyroidism, 4% had haemorrhage, 2% had permanent hypoparathyroidism, 4% had temporary recurrent laryngeal nerve (RLN) palsy and 2% had permanent recurrent laryngeal nerve palsy. Other rare complications were superior laryngeal nerve palsy, hematoma, and wound infection. Conclusion: Improved surgical techniques and proper management of complications reduce the postoperative morbidity and mortality of thyroid surgery. In spite of all measures, keen observation in postoperative period is very important to find out the complications for early intervention. Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 15-19